Necessity of Effective Quality Control System for Bridge Construction (A Review) (Journal of Advances and Scholarly Researches in Allied Education, 2024)
As urbanization quickens and transportation systems proceed to advance, bridges, as indispensably components of urban foundation, confront progressively impressive challenges in their plan and development administration. This inquire about investigates the integration of naturally inviting, financially productive, and socially satisfactory plan standards and development administration strategies in bridge designing from the viewpoint of economical advancement. Through case investigations and information measurements, this paper presents optimized bridge plan arrangements beneath different natural conditions and examines techniques to play down asset squander and improve development effectiveness, in this way accomplishing the feasible improvement objectives of bridge building The quality parameters should easy to understand specially checklists should be easy to understand and easy for implementation In this study is carried out to analyze the scenario of Quality Control System application, to identify factors affecting the construction organization and to issue recommendations on how to improve the implementation of Quality Control System in Construction Industry. The growth in infrastructure increases in our country which leads the construction of new bridges is one most the key elements in this Initially the checklists are observed from different site the defects will identify in check lists and suggest new checklists for each items of construction. This paper finds Necessity of Effective Quality Control System for Bridge Construction by analysising the different Literature review